2012
DOI: 10.1021/ja301802r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Tuning the Catalytic Bias of Hydrogenase

Abstract: When enzymes are optimized for biotechnological purposes, the goal often is to increase stability or catalytic efficiency. However, many enzymes reversibly convert their substrate and product, and if one is interested in catalysis in only one direction, it may be necessary to prevent the reverse reaction. In other cases, reversibility may be advantageous because only an enzyme that can operate in both directions can turnover at a high rate even under conditions of low thermodynamic driving force. Therefore, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
119
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 30 publications
(56 reference statements)
7
119
0
1
Order By: Relevance
“…Attached to an electrode, these enzymes catalyze rapid oxidation and reduction, with only a minimum overpotential being required to swap the current direction either side of the equilibrium potential (2)(3)(4)(5). Of particular interest are hydrogenases, which catalyze the oxidation and production of H 2 with activities that may rival platinum (6)(7)(8)(9)(10)(11) and are inspirational in the quest for future electrocatalysts as well as in artificial photosynthesis (12,13).…”
mentioning
confidence: 99%
“…Attached to an electrode, these enzymes catalyze rapid oxidation and reduction, with only a minimum overpotential being required to swap the current direction either side of the equilibrium potential (2)(3)(4)(5). Of particular interest are hydrogenases, which catalyze the oxidation and production of H 2 with activities that may rival platinum (6)(7)(8)(9)(10)(11) and are inspirational in the quest for future electrocatalysts as well as in artificial photosynthesis (12,13).…”
mentioning
confidence: 99%
“…They are also very active under conditions optimized for a particular direction, operating at up to 20,000 s −1 for H 2 production (5) and 10,000 s −1 for H 2 oxidation (6). Under conditions where reversibility is optimized (3,(7)(8)(9)(10), net turnover frequencies (TOFs) are typically slower. For hydrogenases attached to electrode surfaces, the TOFs are not always quantitated due to uncertainty in surface coverage (9), but in one example, TOFs for a series of mutants of Desulfovibrio fructosovorans [NiFe]-hydrogenase were reported, ranging from 3 to 500 s −1 for H 2 production and 600 to 1,000 s −1 for H 2 oxidation under one set of conditions (8).…”
mentioning
confidence: 99%
“…Although the mechanistic details controlling fast, reversible catalysis in hydrogenases are likely different, the Léger group demonstrated that catalytic bias in [NiFe]-hydrogenase is controlled not by the redox properties of the active site, but by residues remote from the active site that control either H 2 release (H 2 production) or electron transfer (H 2 oxidation) (8). In this model system, we demonstrate that we are controlling H 2 addition and proton transfer with groups remote from the active site, providing a conceptual parallel between the role of the outer coordination sphere in the molecular model and the role of the protein scaffold in the enzymatic system.…”
mentioning
confidence: 99%
“…The amino acids that surround the NiFe active site are conserved (1) and yet the kinetic properties of these enzymes are diverse. For example, some NiFe hydrogenases can oxidize and produce H 2 , whereas others preferentially catalyze one direction of the reaction (2)(3)(4). Another property of some hydrogenases that has attracted considerable interest is their sensitivity (and sometimes their resistance) to O 2 .…”
mentioning
confidence: 99%
“…Substitutions of this amino acid have a strong effect on the rates of intramolecular diffusion (23,24) and, consequently, on the Michaelis constant for H 2 (24), on the catalytic bias of the enzyme (2), and on the rates of inhibition by CO and O 2 (23,24). For example, the V74Q, V74M, and V74E mutants are inhibited by O 2 more slowly than the wild-type (WT) enzyme, but this effect on the rate of inhibition is not strong enough to make the enzyme oxygen resistant.…”
mentioning
confidence: 99%